The influence of financial development towards the international tourism in Malaysia - Goh, Wei Cong; Koh, Bee Shi; Lee, Weng Wei; Gan, Sung Leng; Lee, Shirley Xue Er (2020)
This research paper aim to estimate the influence of financial development towards the international tourism in Malaysia. There are four explanatory variables that include in this research which are financial development, gross domestic product, exchange rate as well as inflation. The data collection for international tourist arrival of Malaysia was from year 1995 until year 2018 which total for 24 years. In this research, domestic credit to private sector is being used for a proxy in the measurement of financial development. The sources of all data was collected from World Bank Group. The data is time series data and Autoregressive Distrubuted Lag (ARDL) model will be used in this research. Besides, Econometrics View (EViews) program was being used to estimate the economic problems and relationship. The result ended up showed a negative relationship between financial development and international tourist arrival of Malaysia.